Dari impor hingga diversifikasi: Analisis strategi ketahanan pangan Indonesia saat krisis global 2007-2008 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
The global food crisis of 2007–2008 significantly impacted food price stability in various countries, including Indonesia. This article aims to analyze the strategies implemented by the Indonesian government in response to the crisis to safeguard national food security. The study adopts a historical approach, employing Kuntowijoyo’s historical method, which includes several stages: heuristic, source criticism, interpretation, and historiography. The analysis reveals that the Indonesian government implemented several measures such as rice imports, the distribution of subsidies through the raskin (rice for the poor) program, and food diversification campaigns to reduce dependency on rice. While these strategies were relatively effective in mitigating short-term impacts, ongoing challenges remain, particularly in terms of import dependency and unequal distribution. Therefore, food security policies in Indonesia require strengthening of the domestic agricultural sector and continuous evaluation to establish a sustainable and inclusive food system.
Keywords: Crisis; Food Subsidies; Food Security Indonesia; Rice Imports